(untitled) (Sebha University Conference Proceedings, 2025)
This Study is related to noise reduction in aircraft and an emphasis on the importance of exhaust pipe design for the auxiliary power units. This study it aims to optimize exhaust pipe layouts as a method of minimizing noise emissions using open-source software and computer modelling. One of the most important subjects for research is investigation of expansion chamber as a potential technique to reduce noise. The sound waves will be absorbed and softened by the placement of chambers inside an exhaust system. The main goal of this study is minimizing the auxiliary power unit’s noise level to ideally under 85 dB and lead to quieter airports and improved noise footprint for surrounding communities. The simulation in this research succeeded in achieving a noise reduction of up to 14 dB compared to original design which had a pressure noise level of 91 dB, resulting in a final noise level below 77 dB.